Mathematics - Lee, Beng Hin; Rohana Ismail; Lee, Khaik Yong; Lim, Meei; Affaf Mohamad (Effective Practice for Matriculation, 2017)
This book is for matriculation semester 1 which is written for students studying mathematics in local matriculation courses. This revision book aims to give students a comprehensive coverage of the type of questions they may encounter in their matriculation examinations.